Исследование диагностической ценности фазовых портретов ЭКГ по данным специализированных баз - Файнзильберг, Л.С.; Лебедушко, Т.Ю. (Кибернетика и вычислительная техника, 2012)
Представлены результаты экспериментальных исследований метода обработки электрокардиограммы (ЭКГ) в фазовом пространстве, основанные на реальных записях ЭКГ интернет-портала PhysioNet. Показаны преимущества использования фазового портрета ЭКГ для оценки дополнительного диагностического признака ишемии миокарда — симметричности фрагмента реполяризации. Представлено результати експериментальних досліджень методу обробки ЕКГ у фазовому просторі, заснованих на реальних записах ЕКГ інтернет-порталу PhysioNet. Встановлено взаємозв'язки традиційних амплітудно-часових ознак ЕКГ у часовій області (депресії та елевації сегмента ST, негативізації зубця T) з формою і параметрами окремих фрагментів породжуваного фазового портрету. Продемонстровано переваги використання фазового портрету ЕКГ для оцінки додаткової діагностичної ознаки ішемії міокарда — симетричності фрагмента реполяризації. The results of experimental studies of ECG processing method in phase space based on real ECG Internet portal PhysioNet has been presented. In the course of these studies the interrelation of conventional amplitude-time characteristics of ECG in the time domain (depression and elevation segment ST, negativization segment T) with the shape and parameters of separate fragments generated by the phase portrait was fitted. These contacts were modeled and validated on real ECG of the Internet portal PhysioNet. This article demonstrated the benefits of using the phase portrait of the ECG to assess the additional diagnostic feature of myocardial ischemia. The processing of real ECG showed that the phase portrait of ECG can more accurately assess the dynamics of changes in the rate of symmetry fragment repolarization than in the analysis of this indicator for the temporary signal.